Membangun Toleransi Dalam Masyarakat Multiagama Dan Multikultural Di Indonesia Dari Perspektif Lukas 10:25-37 - Jacob Songgono (Sekolah Tinggi Teologi Ekumene Jakarta., 2022)
In order to properly carry out the commands and teachings of the Lord Jesus, believers need to understand how to implement them. The article is intended to shed light on their implementation, as stated in the parable of the Good Samaritan in Luke 10:25-37. A narrative approach was used to explore the relevance of the text to the existing context, and then followed by a theological reflection based on the context of Indonesia’s diversity. The reflection on the benevolent attitudes and actions of the Samaritan was disclosed, namely tolerance, compassion and generosity in helping others without discerning religions or cultures. Theological study of the parable was expected to make believers model the Samaritan’s actions assisting neighbors in need. This practice may minimize intolerance occurring in multi-religious and multicultural societies in Indonesia. At the same time, it serves as the implementation of God’s commands, and an embodiment of believers as witnesses and light for Indonesia.